Towards a fully integrated North Sea offshore grid: An engineering‐economic assessment of a power link island. Issue 4 (25th March 2018) - Kristiansen, Martin; Korpås, Magnus; Farahmand, Hossein
Abstract : An increasing share of variable power feed‐in is expected in the next decades in the European power system, with a particularly high offshore wind potential in the North Sea region. This demands more temporal‐ and spatial flexibility in the system, an adequate grid infrastructure can provide both. This study presents an engineering‐economic approach evaluating the impact of novel infrastructure designs towards a fully integrated North Sea offshore grid, including TenneT's vision of a power link island (PLI). A PLI is an artificial island for transnational power exchange and distribution of offshore wind resources. We introduce the concept and evaluate the economic benefits and system implications under three different case studies incorporating 2030 scenarios from European Network of Transmission System Operators. The results demonstrate system cost savings up to 15.8% when comparing a fully integrated PLI solution with traditional, radial typologies. The PLI did in general result in more efficient system dispatch of wind resources, where the involvement from Norway, Great Britain, and Germany occurred most frequently in terms of grid reinforcements and expansions. This article is categorized under: Wind Power > Systems and Infrastructure Energy Infrastructure > Systems and Infrastructure Energy Systems Economics > Systems and Infrastructure Abstract : Conceptual illustration of the power link island. Each island can hub 30 GW offshore wind capacity, with an aggregated potential to hub 100 GW using multiple islands.